Insights from a Teaching Assistance Program in Thailand: A Scientific Literacy Analysis of a Lower Secondary Science Textbook - Agustin Intan Permatasari; Fajar Dinar Maftukh; As’ari; Rorsi Che Muda (Science Education and Application Journal, 2026)
This study was conducted in response to the growing importance of scientific literacy as a key competence for students in the 21st century, particularly in relation to global challenges and evidence-based decision making. The research aims to analyze the presentation of scientific literacy in the Science and Technology textbook for Mattayom 3 Semester 2 used at Ban Kayae School, Narathiwat, Thailand, and to describe its strengths and limitations based on the OECD scientific literacy framework. A qualitative approach with content analysis design was employed. The unit of analysis included all chapters, learning activities, illustrations, and evaluation tasks in the textbook. Data were collected through documentation, checklist sheets based on three OECD competencies, and semi-structured interviews with two expert validators. Data were analyzed through coding, percentage calculation, and inter-rater agreement using Cohen’s Kappa. The results indicate that the textbook integrates the three core competencies of scientific literacy: explaining phenomena scientifically (35.1%), evaluating and designing scientific inquiry (32.4%), and interpreting data and evidence for decision making (32.2%), with relatively balanced distribution across chapters. Although certain chapters emphasize particular competencies, the book does not solely focus on conceptual knowledge but also incorporates inquiry and application aspects. The textbook is structurally aligned with OECD indicators and is considered worthy as a model for literacy-oriented science textbooks. Future development should strengthen authentic inquiry activities, contextual data analysis, and visual clarity to further enhance scientific literacy integration.